Design of Physics Learning Media Using Mind Map-Based Cloud Persentation in Optical Instruments Material - Lelfita; Eka Susanti; Nelfi Erlinda; Roni Febriandi (Jurnal Penelitian Pendidikan IPA, 2024)
Mind map provide a creative display of topic network under discussion in learning process. Therefore, the integration of mind map in learning media is an alternative way to increase student’s interest. We designed mind map-based learning media to deliver optical instruments material and evaluate its properness in XI grade of SMA N 15 Padang. This is an R&D research using modified Brog and Gall development used a mixed method between qualitative and quantitative approach. Learning media was validated by material expert, media expert and a physics teacher. The validation results from three validators are obtained with an average of 88%, 93% and 88% which is categorized as very worthy and this media is feasible to be applied. Student responses on media assessment showed very agree with 46.63%, agreed with 41.6%, only 9.49% chose Less Agree and 2% chose Disagree. Students admitted that the mind map was interesting, easy to use, and helpful. Therefore, the mind map learning media in optical instrument is appropriate to apply in learning process.